Role of Nutrition in the Management of Diabetes Mellitus - Shravan Kr. Paswan; Pritt Verma; Abhisek Raj; Lubna Azmi; Sajal Shrivastava; Ch. V. Rao (Asian Pacific Journal of Health Sciences, 2016)
A healthful eating pattern, regular physical activity, and often pharmacotherapy are key components of diabetes management. For many individuals with diabetes, the most challenging part of the treatment plan is determining what to eat. It is the position of the American Diabetes Association (ADA) that there is not a “one-size-fits-all” eating pattern for individuals with diabetes. The ADA also recognizes the integral role of nutrition therapy in overall diabetes management and has historically recommended that each person with diabetes be actively engaged in self-management, education, and treatment planning with his or her health care provider, which includes the collaborative development of an individualized eating plan. Therefore, it is important that all members of the health care team be knowledgeable about diabetes nutrition therapy and supports its implementation.